Inseminación artificial de alpacas con semen colectado por electroeyaculador ajustado a 2 voltajes. - Masabanda Soria, Eddy Bryan (2020)
This research was conducted at the Salache Experimental Center. The artificial insemination of alpacas with fresh collected semen using electro-ejaculation adjusted to 10 voltages and 12 voltages, where 4 dentures previously used for evaluation WHERE were used to estimate their age (booting technique), body condition, health status, size, shape, consistency, and testicles elasticity and epididymis as the conditions of the foreskin and penis. The training was done so that the male unsheathed correctly at the time of electroejaculation. The diluent was selected and the acquisition, the semen extraction method and its collection were identified by the selected technique. The rectal technique was performed, where the stools were removed before the electro ejaculator introduction by using 10 and 12 voltages for the seminal ejaculate extraction. Determining the voltage level response on the quantity and ejaculate quality using the technique used, later in the laboratory, the macroscopic (color, volume, pH) and microscopic characteristics (sperm concentration, individual and mass motility and mass and mortality) were evaluated) by using commercial diluent. Where a greater ejaculate at 12 volts level was obtained in the technique used to 10 volts. Artificial insemination was carried out in 4 alpacas with collected semen by electro-ejaculation diluted in fresh with the commercial Andromed diluent after its extraction and evaluation at the laboratory.